Direito indígena à saúde: proteção constitucional e internacional - Oliveira, Paulo Henrique de (2009)
This essay aims to examine indigenous peoples right to health, particularly its protection by Brazilian constitutional law and by international law. Since colonial times indigenous peoples health are inferior to non-indigenous. Several indigenous communities experience dire health conditions, with numerous casualties, especially within children, in virtue of the lack of medical care. Such poor conditions are worsened by ethnic transfiguration, environmental degradation and indigenous impoverishment. Notwithstanding, indigenous peoples rights and, in particular, its right to health have been gaining strength in constitutional and international human rights law. In this scenario, emerges the challenge of articulating constitutional and international regulation, in order to render indigenous peoples right to health effective. To that purpose, it is necessary to investigate how the law defines indigenous peoples; the constitutional evolution of indigenous rights; the constitutional principles of indigenous peoples right to health; the international recognition of indigenous peoples human rights and the international protection of the right to health